“GASTRONOMIA ÁRABE: PATRIMÔNIO CULTURAL DE FOZ DO IGUAÇU (PR)” - Domingues, André Ricardo (2015)
This work aims to recognize Arabic cuisine as one of the cultural heritage of Foz do Iguaçu city through a geographic approach. Therefore, we sought to understand how immigrants and Arab descendants established their social relations, that is; as the colony of Arab immigrants relates on everyday life and the cultural socio reality of that city. By analyzing Arab cultural influences in Foz do Iguaçu, one of the most obvious is the cuisine, and the wide range and location of the Arab gastronomic establishments in the commercial center of the city means this process by territoriality. By studying the immigration process of the Arab community in Brazil and Foz do Iguaçu, they present two distinct moments mass immigration of Arabs to Brazil. The causes of their choice by Foz do Iguaçu were the opening of the Paraguayan trade and the search for quality of life offered in the west of Paraná. The survey also shows a relationship between cultural identity formation localities through the presence and gastronomic contributions brought by immigrant groups, and from this premise, there is the cultural heritage approach established by research. To highlight the representation of Arab immigrants in Foz do Iguaçu, in addition to literature searches, we use a spatial picture of the location of gastronomic equipment with Arab identity as well as pictures of some of the Arab representation spaces in Foz do Iguaçu. Restaurants, snack bars and shawarmarias listed in the spatial figure were analyzed and described the work of the body as well as your offer. The association between the Arab gastronomic offer with the tourist activity in the city, it was found that the city is not a tourist destination where the main attraction is the gastronomic tourism, but on the other hand, the food in question surprises visitors by its offer and visibility, thus a differential to Foz do Iguaçu as a tourist destination.